2011
DOI: 10.5194/hess-15-3829-2011
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of ASCAT near-surface soil moisture into the SIM hydrological model over France

Abstract: Abstract. This study examines whether the assimilation of remotely sensed near-surface soil moisture observations might benefit an operational hydrological model, specifically Météo-France's SAFRAN-ISBA-MODCOU (SIM) model. Soil moisture data derived from ASCAT backscatter observations are assimilated into SIM using a Simplified Extended Kalman Filter (SEKF) over 3.5 years. The benefit of the assimilation is tested by comparison to a delayed cut-off version of SIM, in which the land surface is forced with more … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 40 publications
(42 reference statements)
4
117
0
Order By: Relevance
“…The choice of the data assimilation algorithm turned to be more consistent in this period. The majority of studies chose the ensemble Kalman filter (EnKF) [102][103][104]180,182,183,185,191,196,198], while just a few used nudging [186], hard updating [192] and EKF [197]. There were also few particle filter (PF) applications.…”
Section: Model Types For Rs-sm Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the data assimilation algorithm turned to be more consistent in this period. The majority of studies chose the ensemble Kalman filter (EnKF) [102][103][104]180,182,183,185,191,196,198], while just a few used nudging [186], hard updating [192] and EKF [197]. There were also few particle filter (PF) applications.…”
Section: Model Types For Rs-sm Assimilationmentioning
confidence: 99%
“…Beside a couple of tests using synthetic RS-SM data [104,185,196], ASCAT [102,103,182,184,186,191,192,197], AMSR-E [103,180,182,192] and SMOS [102,103,182,183,198] soil moisture products were widely implemented during this period. Simultaneously assimilating multi-source RS-SM products has also been tested recently [102,103,182,192].…”
Section: Model Types For Rs-sm Assimilationmentioning
confidence: 99%
“…Recent studies showed that assimilation of soil moisture data into hydrologic modeling 20 could improve water balance predictions such as evaporation and runoff (e.g. Crow et al, 2017;Mohanty et al, 2013;Brocca et al, 2012;Matgen et al, 2012;Draper et al, 2011;Pauwels et al, 2002;2001). However, many of these studies mainly focused on improved predictions at watershed scales using in situ observations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these instruments generally measure soil moisture at relatively shallow layers. For example, microwave remote sensing methods (either active or passive) retrieve near-surface soil moisture that only reaches several centimetres beneath the soil surface (Draper et al, 2011). Therefore, it is necessary to link surface soil moisture to profile soil moisture via robust depth-scaling approaches.…”
mentioning
confidence: 99%
“…Data assimilation methods refer to techniques which incorporate surface soil moisture measurements (e.g. remote sensing products) into physically-based hydrologic models to obtain an analysis that best represents profile soil moisture and a number of data assimilation algorithms have been developed (Evensen, 1994;Walker et al, 2002;Heathman et al, 2003;Reichle et al, 2007;Draper et al, 2011;Dumedah et al, 2015). However, its application may be constrained by the required model parameters (soil properties, vegetation features and atmospheric forcing), which are difficult to obtain at larger scales, as well as by uncertainties related to the physical description of soil hydrological processes (Albergel et al, 2008;Hu and Si, 2014).…”
mentioning
confidence: 99%